Layanan Penerapan Karbon Aktif Sebagai Media Penyaring Air di Lingkungan SMA Negeri 4 Jayapura - Khaeriah Dahlan; Mikha M. Kawari; Hana I.K. Bella; Octolia Togibasa (Bakti Hayati: Jurnal Pengabdian Indonesia, 2022)
Activated charcoal can be used as filter for water contaminant and also heavy metals absorbance. The aims of this action were to provide information and introduce the application of activated charcoal as a filter media for contaminated water. This activity was conducted at SMA Negeri 4 Jayapura by using seminar method for sharing the information. The output of this activity can be seen from the understanding of participants regarding the basic knowledge and also the use of activated charcoal for several functions.Keyword: fresh water; activated charcoal; water filter.Â